Mesa Redonda Complex (Villaverde del Río, Seville): a tell above the Lower Guadalquivir Valley - Marta Diaz-Zorita Bonilla; Martin Bartelheim; Döbereiner Chala-Aldana; Javier Escudero Carrillo; Francisco José García Fernández; Eduardo Ferrer Albelda; Pablo Garrido González; Fernando Daza Pastrana (Trabajos de Prehistoria)
The archaeological site of Mesa Redonda (Villaverde del Río, Seville) was the subject of archaeological research at the end of the 1970s, and only recently has new research been carried out. In this paper we present the results of both the old and the new archaeological work conducted in 2019-2021. We have named this site the Mesa Redonda Complex, because of the wider period of use and because it includes many different sites. According to the results of the archaeological survey, test pits and geoelectric prospection, the archaeological site offers a multi-layered continuous use of the summit from the Bronze Age to the Islamic Middle Ages (12th century AD). Due to its size and long diachronic sequence, in this case covering at least four millennia, the structure of the site complies with the definition of an archaeological tell. Mesa Redonda is strategically located between the Guadalquivir Valley and Sierra Morena, overlooking the fertile lands of the valley with abundant agropastoral resources.